Massive Periacetabular Osteolysis Treated With Acetabular Cup Retention and Cemented Screw Fixation - Isabella T. Wu, MD, MPH; Cary S. Politzer, MD; Frank Chiarappa, MD; Scott T. Ball, MD (Arthroplasty Today)
Management of periacetabular osteolysis is a challenging dilemma in revision total hip arthroplasty. When the acetabular shell is well-fixed, the surgeon may prefer to retain the cup to minimize further bone loss. However, filling the surrounding defect can be difficult if the area of involvement is massive. In this case, holes were created in the existing acetabular cup for supplemental pelvic screws, which were placed using computed tomography navigation, and then the areas of osteolysis were filled with cement. The patient recovered uneventfully, and he was satisfied with the outcome at 4 years postoperatively. Thus, pelvic screw placement with cement augmentation could be a viable option for a stable cup with surrounding osteolysis. Patient selection should be considered carefully as the long-term outcomes of this procedure are unknown.